2011
DOI: 10.1186/1475-2875-10-225
|View full text |Cite
|
Sign up to set email alerts
|

The architecture and effect of participation: a systematic review of community participation for communicable disease control and elimination. Implications for malaria elimination

Abstract: BackgroundCommunity engagement and participation has played a critical role in successful disease control and elimination campaigns in many countries. Despite this, its benefits for malaria control and elimination are yet to be fully realized. This may be due to a limited understanding of the influences on participation in developing countries as well as inadequate investment in infrastructure and resources to support sustainable community participation. This paper reports the findings of an atypical systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
235
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(241 citation statements)
references
References 84 publications
(539 reference statements)
4
235
0
2
Order By: Relevance
“…Such research aims to identify potential participantsā€™ beliefs, values, attitudes, knowledge and behaviors related to the health problem of interest and provide insight into key aspects of the local context [31,32]. With regard to malaria control programs, past failures of ā€˜one size fits allā€™ has prompted the development of a tailored approach [33]. Recently in Nigeria, such formative research was found valuable in designing the tailored chemoprevention intervention for malaria [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such research aims to identify potential participantsā€™ beliefs, values, attitudes, knowledge and behaviors related to the health problem of interest and provide insight into key aspects of the local context [31,32]. With regard to malaria control programs, past failures of ā€˜one size fits allā€™ has prompted the development of a tailored approach [33]. Recently in Nigeria, such formative research was found valuable in designing the tailored chemoprevention intervention for malaria [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recently in Nigeria, such formative research was found valuable in designing the tailored chemoprevention intervention for malaria [34]. Nevertheless, in many malaria control programs, to date, little formative research has been reported in term of informing community engagement [11,33]. For Lao TME, quantitative and qualitative methods were essential to design engagement strategies for particular village and sub-villages.…”
Section: Discussionmentioning
confidence: 99%
“…It is through empowerment that communities gain mastery over their lives and change their social and political environment to improve their health and quality of life (Wallerstein [22]). Since multiple reviews have argued the value of community participation [4]- [12], evaluations have largely focused on health outcomes. None assess the extent to which community participation figures in research on health systems interventions.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been enshrined as an important standard within rights based approaches to health that has a basic value in and of itself [3]. Since these landmark agreements reinforce community involvement, considerable experience has been built regarding it, with plenty of argue and reflection about its definition, rationale and outcomes [4]- [12]. Community involvement can be instrumental as working with communities can help make interventions more relevant to local needs, informed by local knowledge and priorities, and therefore more effective.…”
Section: Introductionmentioning
confidence: 99%
“…Community participation at multiple levels is an important factor to achieve locally meaningful responses towards further malaria control and sustain the achieved gains (Atkinson, Vallely, Fitzgerald, Whittaker, & Tanner, 2011). One approach towards sustainability of used interventions is effectively engaging with all stakeholders.…”
mentioning
confidence: 99%